Relationship between technical competency and extensionists' job performance - Neda, Tiraieyari; Idris, Khairuddin; Hamzah, Azimi; Uli, Jegak (INSInet Publication, 2009)
This study was to determine the relationship between technical competency and extensionists’ job performance in relation to Good Agricultural Practice (GAP) among Malaysian extensionists at Department of Agriculture (DOA). The study employed stratified random sampling technique. Samples are chosen with a technique called proportional sample allocation. The sample consisted of 210 extensionists from Department of Agriculture in four states of Malaysia. The data were analyzed using descriptive statistics and Pearson correlation analysis. The findings support the positive relationship between technical competency and job performance. Finding would help policy makers and extension managers to focus on development of competent extensionists as the whole extension process is depend on extensionists to transfer GAP to the clients. Competency identified in this study could be incorporated into in-service training as well.